Perancangan Interior Pusat Fotografi Berbasis Co-Working Space di Surabaya - Janice Salim; Sriti Mayang Sari; Jean Francois Poilot (Intra, 2018)
Photography has been progressing and developing rapidly in recent years. It can be a business that is promising and much sought after by consumers from various backgrounds. To support this business, a facility that can accommodate photography activities especially for start-up entrepreneurs, is needed. Therefore, the designer comes up with an idea to design a photography center based on co-working space in Surabaya that can facilitate start up photography businesses as well as to accommodate meetings among photographers and between photographers and their clients. The design method used consists of 7 stages: (1) Inquiry, (2) Empathize, (3) Define, (4) Brainstorm, (5) Prototype, (6) Test, (7) Apply & Reflect. The design concept applied is Dynamic Interfusion. This concept is appointed to be the solution of the problem, which is the activity of photography that tends to be individual and leads to lack of interaction. This concept is applied in the design into an open space layout, creating the impression of motion, flexible and multi-functional rooms. Main facilities designed include store, gallery, plain and thematic photo studio, communal lounge, editing room, meeting room, and workshop area. Also equipped with supporting facilities such as lobby, cafe, makeup and dressing room, management office, pantry, storage, and toilet.